Visual Basic 2005 Recipes A Problem-Solution Approach - Rajan, Rakesh; MacDonald, Matthew; Herman, Todd; Jones, Allen (Apress : Imprint: Apress, 2007)
Whatever your situation, one thing is certain: you will always know what you want to do, but not necessarily how best to do it. This book has been written to help you through those difficult decisions and is an invaluable companion when tackling a wide range of Visual Basic 2005 problems. Mastering .NET development is as much about understanding the functionality of the .NET Framework as it is about the syntax and grammar of your chosen language. Visual Basic 2005 Recipes: A Problem-Solution Approach recognizes this fine balance. This book meets your need for fast, effective solutions to the difficulties you encounter in your coding projects. The recipes have been chosen with professional developers in mind and feature a careful balance of code and text. The code gives you everything you need to solve the problem at hand, while the accompanying text carefully explains how it solves your problem and, more importantly, why it works the way it does.